Analisis Zat Gizi Makro Dari Tepung Kombinasi Kakao (Theobroma Cacao L) dan Ubi Kayu (Manihot Utilissima) Sebagai Bahan Dasar Biskuit - Hairunnisa Hairunnisa; Suherman Suherman; Supriadi Supriadi (Jurnal Akademika Kimia, 2017)
This study aims to determine the moisture content, ash, carbohydrate, protein and fat from a combination of flour cocoa and cassava as a raw material manufacture of biscuits, as well as knowing the favorite test (favorite level) of the biscuits that have been made with several variations of flour cocoa and cassava. The method used is the gravimetric method, combustion method, phenol method, Kjeldahl method, and soxhlet method.The results showed that the combination of cocoa powder and cassava with some variation of that, variation A (25%:75%) had a moisture level of 18.0%, 2.2% ash, 2.7 mg/100gcarbohydrates, 1.7% protein, and 7.2% fat. Variation B (50%: 50%) had a moisture level of 4.0%, 3.4% ash, 63.9 mg/100 g carbohydrates, 4.8% protein, and 19.2% fat. Variation C (75%:25%) had a moisture level of 2.0%, 9.4% ash, 127.9 mg/100gcarbohydrates, 6.7% protein, and 27.4% fat. These results indicated that the levels of nutrients in the combination of cocoa and cassava flour increased with increasing variations, especially for ash, carbohydrates, protein, and fat levels with the addition of cocoa flour by 75% but the moisture level decreased, and the biscuit trials have shown that the best treatment was the Variation B (50%: 50%).